Investigating oil mixture flow characterization - Mei, Charlotte Kho Sui (2013)
In this research the high viscosity of crude oil exerts high turbulences creates the resistance (drag) and lower the mobility and flow of the crude oil. Thus, more power is needed to transport the fluid. This research is to investigate oil mixture performance when addictives are introduced into the system. In this experiment, the performance the addictives used are non – ionic surfactants, Triton X – 15 and Triton X – 114 are added into the oil mixture to form emulsions and the samples are tested using rotating disk apparatus. The investigate parameters are effect of the concentration of surfactant, volume fraction of oil and water, rotational speed and types of surfactant used to the emulsion. The torque value (flow resistivity) measured varies with the rotational speed up tested from 50 rpm to 3000 rpm and the emulsion concentration at 600 ppm, 800 ppm and 1000 ppm. Besides, different volume of water: oil ratios (50% - 50%, 60% - 40%, 70% - 30%) are also investigated. Triton X – 114 has high potential in enhancing the transportation of crude oil via pipelines as emulsions formed that contains 40% oil and 60% water shows torque reading less than the torque value exerted by the cooking oil without any addition of addictives. The reduction of torque is approximately 50% lower than the cooking oil without any addictives. It is proven that Triton X – 114 lowers the surface tension of the fluid thus it reduces the flow resistivity. The Triton X – 15 is strongly not recommended in forming emulsion for transportation as it exerts high resistance in the form of an emulsion. It is strongly recommended for future work that the study should be done in larger scope on certain experimental parameters specifically on more addictives should be tested. Besides that, the more rheological studies should be expanded on the effect of temperature, concentrations and volume fractions on the performance of emulsion Besides, it is better if the formation of droplets on the emulsion size in order to have a better the understanding of the factors contributes to emulsions stability